2019
DOI: 10.1080/00071668.2018.1556388
|View full text |Cite
|
Sign up to set email alerts
|

Feed processing and structural components affect starch digestion dynamics in broiler chickens

Abstract: 1. A 2x2 factorial design was used to test the hypothesis that impaired intestinal starch digestibility is attributable to rapid passage of digesta from the gizzard to the intestine, and that compared to steam pelleting, increasing the availability of starch through extrusion cooking may alleviate the potential negative effect of rapid digesta flow on starch utilisation. 2. Thus, 7-d-old broilers chickens were distributed to 48 cages and given a wheat-based (WB) pelleted diet containing either coarse oat hulls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
1
6
1
Order By: Relevance
“…Contrary to the findings of Itani and Svihus (2019), there was no difference in starch digestibility between pelleted and extruded wheat diet in the current experiment. Thus, it can be suggested that the presence of other factors may have maximised the digestion of wheat starch in the pelleted diet and masked the effect of increased gelatinisation in the extruded wheat diet.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to the findings of Itani and Svihus (2019), there was no difference in starch digestibility between pelleted and extruded wheat diet in the current experiment. Thus, it can be suggested that the presence of other factors may have maximised the digestion of wheat starch in the pelleted diet and masked the effect of increased gelatinisation in the extruded wheat diet.…”
Section: Discussioncontrasting
confidence: 99%
“…As expected, and in agreement with other studies (Itani and Svihus 2019;Zimonja and Svihus 2009), extrusion resulted in a more extensive starch gelatinisation compared to pelleting. Although pelleted diets had a similar amount of gelatinised starch (209 and 207 g/kg in the wheat and FBS diet, respectively), extrusion increased the proportion of gelatinised starch in the FBS (943 g/kg) compared to the wheat diet (715 g/kg).…”
Section: Discussionsupporting
confidence: 93%
“…Increased ceca weight in broilers fed pelleted feed relative to broilers fed mash-fed was linked to increased flow of undigested starch in the ceca leading to increased fermentation capacity (35). In a more recent study addition of oat hulls in pelleted wheat diet increased gizzard weight and holding capacity (83). Further studies are needed to determine the mechanism behind the stimulation effects of HTP on gut physiology, morphology and immunology.…”
Section: Histomorphologymentioning
confidence: 99%
“…As observed before in experiments with turkeys ( Jackson and Duke, 1995 ), refeeding of birds which have been starved to empty will result in the entire length of the small intestine becoming filled with contents within an hour. Experiments have demonstrated that birds with an underdeveloped gizzard due to lack of structural components in the form of the insoluble fibre oat hulls (compared with a finely ground cellulose control) will allow for a very rapid flow of feed material into the small intestine when starved and then refed ( Sacranie et al., 2017 ; Itani and Svihus, 2019 ). Although the flow is surprisingly fast independent of gizzard function, the amount that bypassed the gizzard was observed to be considerably larger for birds without a well-functioning gizzard.…”
Section: The Role Of Dietary Fibre In the Functional Development Of T...mentioning
confidence: 99%
“…However, no such effects have been observed in experiments with isonutritious diets where finely ground and coarsely ground fibre has been compared ( Sacranie et al., 2012 ; Svihus et al., 2013a , Svihus et al., 2013b ; Itani and Svihus, 2019 ). In fact, Sacranie et al.…”
Section: The Role Of Dietary Fibre In the Functional Development Of T...mentioning
confidence: 99%